Charting the Roots of Anti-Chinese Populism in Africa: A Comparison of Zambia and Ghana. (April 2014) - Hess, Steve; Aidoo, Richard
In this article the authors conduct focused case studies on Zambia and Ghana to investigate the increasingly diverse popular reactions to Chinese engagement throughout the region of sub-Saharan Africa. In this effort they challenge the existing binary exploitation/opportunity paradigm through which growing Chinese engagement in sub-Saharan Africa is often analyzed. Instead, they propose an alternative framework, which centers less on the positive or nefarious nature of Chinese involvement and more on the institutional structures of African regimes. As opposed to closed autocracies and consolidated multiparty democracies, fluid transitional states create opportunities for the appearance of anti-Chinese populist movements akin to Michael Sata and the Patriotic Front in Zambia.